The Photoluminescence Properties of Ablated ZrO2 Nanoparticles - A.P. Kuzmenko; M.A. Pugachevsky; M.B. Dobromyslov (Журнал нано- та електронної фізики)
The method of optical spectroscopy determined photoluminescence properties of zirconia nanoparticles produced by laser ablation. The effect of annealing of nanoparticles in the range from 400 to 1000 °C on their luminescence is investigated. It is shown that the emission of the luminescence make it possible to conclude about the type of defects in the structure of nanoparticles and their dynamics during annealing. A qualitative explanation of the detected patterns is provided.